2013
DOI: 10.1007/s00425-012-1832-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the TMV resistance gene N prevents a hypersensitive response in seeds and during germination

Abstract: The dominant tobacco mosaic virus (TMV) resistance gene N confers a hypersensitive response (HR) at the site of TMV infection and protects tobacco against systemic spread of the virus. To study N gene activity in seeds and early seedling development, the avirulence gene of N, the helicase domain (p50) of the TMV replicase, was constitutively expressed in a tobacco genotype without N (nn). Transgenic F1 expressing N and p50 were generated by crossing with an NN genotype. Surprisingly, Nn F1 seeds expressing p50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“… 58 The N gene encodes two alternatively spliced mRNAs that possess a TIR domain, a NB domain, and a LRR, all of which are required for N function. 59 , 60 RT-qPCR analysis indicated that the N gene had a higher level of expression in ‘Su Shuai’ compared with ‘Golden Delicious’ and ‘Indo’. The MbR7 homologous gene (MDP0000233155) encodes a TIR-NBS-LRR type R protein 7.…”
Section: Discussionmentioning
confidence: 99%
“… 58 The N gene encodes two alternatively spliced mRNAs that possess a TIR domain, a NB domain, and a LRR, all of which are required for N function. 59 , 60 RT-qPCR analysis indicated that the N gene had a higher level of expression in ‘Su Shuai’ compared with ‘Golden Delicious’ and ‘Indo’. The MbR7 homologous gene (MDP0000233155) encodes a TIR-NBS-LRR type R protein 7.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation rate of the N gene in wild-type tobacco (i.e., lacking the avirulence transgene P50) was also high. Second, the N gene is not expressed during embryogenesis or in young seedlings (Niemeyer et al, 2013). In other words, no HR stress should occur at these stages of development.…”
Section: Discussion Frequent Loss Of Function Of the N Gene Is Not Caused By Stressmentioning
confidence: 99%